THE INFLUENCE OF PROJECT-BASED LEARNING MODELS ON IMPROVING STUDENTS' CREATIVITY IN SOCIAL STUDIES SUBJECTS AT STATE JUNIOR HIGH SCHOOL 1 SINJAI - Nuralif, Nuralif; Hasni, Hasni; Ibrahim, Ibrahim; Shasliani, Shasliani; Adriani, Nour Muhammad (Social Landscape Journal, 2025)
The development of 21st-century education demands innovation in the learning process that not only focuses on mastering subject matter but also on fostering students’ creativity as a vital skill to face global challenges. However, in reality, students’ creativity in social studies learning is often not optimally developed due to the use of conventional teaching methods. This study aims to examine the implementation of project-based learning at SMP Negeri 1 Sinjai, describe students’ creativity in social studies subjects, and analyze the effect of project-based learning on enhancing students’ creativity in social studies. This research employed a quantitative approach with an ex-post facto design. The variables consisted of project-based learning (X) and students’ creativity (Y). Data were collected through observation, questionnaires, and documentation, while data analysis was conducted using descriptive and inferential statistics with the assistance of SPSS 25. The results indicate that project-based learning is implemented at a “very high” level, characterized by decision-making centrality, focus on driving questions, constructive investigations, autonomy, and realism. Furthermore, students’ creativity in social studies is also categorized as “very high,” with indicators including fluency, flexibility, originality, elaboration, and sensitivity. Additionally, there is a positive and significant effect of project-based learning on students’ creativity, with a correlation coefficient of 0.725 categorized as “strong.” These findings confirm that the implementation of project-based learning is effective in enhancing students’ creativity in social studies.